2011
DOI: 10.1007/s00404-011-2141-1
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of inhibitors of DNA binding/differentiation gene during alendronate-induced osteoblast differentiation

Abstract: PurposeTo investigate the effect of alendronate on the expression of Id genes in osteoblast differentiation.MethodsC2C12 cells were treated with alendronate for various concentrations and time periods. For evaluation of alendronate-induced osteoblast differentiation in C2C12 cells, alkaline phosphatase (ALP) activity was measured. The expression of osteoblast differentiation markers such as ALP, type-1 collagen (Col 1), and osteocalcin (OCN), and the expression of Id-1 and Id-2 were measured by RT-PCR. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…In the present study, it was identified that there was a significant difference in the level of runx2 between the control group and the sham group; this may be due to suppression of osteogenic growth following implantation of the prosthesis. Results of an in vitro study by Kang et al (45), examining the effects of ALN on osteoblasts, are inconsistent with the present results; this discrepancy may be caused by the difference in experimental materials. The study conducted by Kang et al was an in vitro experiment, whereas the present study observed effects in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, it was identified that there was a significant difference in the level of runx2 between the control group and the sham group; this may be due to suppression of osteogenic growth following implantation of the prosthesis. Results of an in vitro study by Kang et al (45), examining the effects of ALN on osteoblasts, are inconsistent with the present results; this discrepancy may be caused by the difference in experimental materials. The study conducted by Kang et al was an in vitro experiment, whereas the present study observed effects in mice.…”
Section: Discussioncontrasting
confidence: 99%
“…This is strongly supported by a previous study, 12 although some studies have shown that ALN treatment induces osteoblast differentiation and bone formation. 13,16 The difference could possibly be due to experimental systems used, including cell types, stages of cell differentiation (stem cells/osteoprogenitors vs. osteoblastic cells) and ALN concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability was determined using an MTT assay method previously reported . Cells were plated at a density of 1.0 × 10 4 per cm 2 in 96‐well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was determined using an MTT assay method previously reported. 21 Cells were plated at a density of 1.0 × 10 4 per cm 2 in 96-well plates. After reaching confluence, ZOL and ETI were added to the culture medium, then medium was removed at various time points and replaced with 50 μL of a solution containing 12.5-μg MTT, then further incubation was performed at 37°C.…”
Section: Mtt Assaymentioning
confidence: 99%